The United States in Asia and China in Latin America, Changes in the New Hegemonic World Map - López Villafañe, Víctor (2012)
The objective of the article has two main goals. On one hand, we want to study US hegemony in the East Asia; how it proceeded there and challenges posed by other international powers. US hegemony in Asia was resolutely established after the victory over Japan in 1945. Nevertheless since the rise of the Chinese economic power and its role now as second world economic power the US ispassing from the Japanese containment to a Chinese containment, adopting trade and military strategies to achieve this objective. In the second part of the article Chinese economic penetration to Latin America is going to be reviewed and if it is representing a hegemonic challenge to the US supremacy which is adopting new trading policies as complementary tool after the FTAA failed into the region in order to maintain its hegemony. Finally, the article offers concluding remarks with specific characteristics on how hegemonic competence is carried out and consequences in both regions, Asia and Latin America.